The Effect of Training on Emotional Intelligence on Improving Social Participation of Students at Mutah University - Ahmad Abdullah Al-Tarawneh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the effect of a training program based in emotional intelligence in developing social participation among a sample of Mutah University students, because of its importance in preparing university students for social participation, expanding this concept for them, and making them able to assume responsibilities, and face pressures The experimental method was used in the study, the sample consisted of (64) students selected via a convenient method they were distributed to an experimental group (n=32) and a control group (n=32). To achieve the objectives of the study, a training program based on emotional intelligence was developed, and data was collected using the Social Participation Scale, which consists of 51 items distributed over four dimensions. The results showed that there were statistically significant differences at the significance level (0.05) between the experimental and control groups in favor of the experimental group on the dimensions of the social participation scale and on the total score. The study recommends conducting more studies to examine the relationship between emotional intelligence and social participation in other samples of students at Mutah University, in other colleges than the College of Educational Sciences, and in other universities, and employing the training program by those interested in the field of social participation.